(untitled) (Revista Cientifica Ingenio Magno, 2020)
This research studied the potential for regeneration of aluminum, by removing metal in an acid solution of two types of water sludge (dry sludge and fresh sludge) from the Drinking Water Treatment Plant of the Municipality of Aguazul Casanare. In addition, this study carried out a jar test with the recovered aluminum solutions of higher concentration, in order to establish the optimal pH and analyze the turbidity and color conversion parameters to the values required in Colombian regulations for drinking water. An aluminum recovery at pH of 1.9 in dry and fresh sludge of 18,35 and 58,75%, respectively as a result. Besides, aluminum concentrations in dry and fresh sludge were 3.900 y 2.600 mg/L. The jar test of water of PTAT of Aguazul with the greatest removal of color and turbidity was obtained using the dry sludge recovered at pH 1.9 at an optimal dose of 25 mg/L of aluminum, with the color and turbidity removals being 77.4 and 84.1%, respectively.